Human SHQ1 variants R335C and A426V lead to severe ribosome biogenesis defects when expressed in yeast - Alidou-D’Anjou, Ismaël; Patel, Aniket; Sleiman, Sophie; Dragon, François (Frontiers in Genetics, 2023)
SHQ1 is an essential chaperone that binds the pseudouridine synthase dyskerin in the cytoplasm and escorts the enzyme to the nucleus, where dyskerin is assembled into small nucleolar RNPs (snoRNPs) of the H/ACA class. These particles carry out pseudouridine formation in ribosomal RNAs (rRNAs) and participate in maturation of rRNA precursors (pre-rRNAs). Variants of human SHQ1 have been linked to neurodevelopmental deficiencies; here we focused on two compound heterozygous mutations identified in a child showing a severe neurological disorder comprising cerebellar degeneration. To investigate the molecular defects caused by mutations R335C and A426V we used a conditional yeast strain that can be depleted of the endogenous Shq1 protein while constitutively expressing human SHQ1 (wild-type or variants). Although wild-type SHQ1 complemented the Shq1-depleted strain, cells expressing variant R335C could not support growth, and cells expressing variant A426V were temperature-sensitive. When shifted to restrictive conditions, yeast cells progressively lost H/ACA snoRNAs and accumulated unprocessed pre-rRNAs, which led to reduced production of ribosomes. Levels of Cbf5 (yeast homologue of dyskerin) were decreased in yeast cells expressing SHQ1 variants under restrictive conditions. Immunoprecipitation experiments revealed that interaction of Cbf5 with SHQ1 variants was weakened but not abolished, and yeast two-hybrid assays showed that mutation R335C is more deleterious than mutation A426V. Our data provide additional evidence for the critical role of SHQ1 in chaperoning the pseudouridine synthase dyskerin, and how its inadequate function has detrimental consequences on the production of H/ACA snoRNPs and ribosomes.